The impact of marketing mix towards customer’s awareness in unit trust investment / Mohd Ekhsan Bazli Jalius - Jalius, Mohd Ekhsan Bazli (Faculty of Business and Management, 2009)
There are important to be able to manage one’s personal finance such as planning for long term investment for retirement and education purposes. People must also decide where and when to save their money in order to avoid difficulties when unexpected events take place. There are several ways for the financial planning such as saving, investment and the like. In the course of regular person’s life, the exposure to finance and financial planning may start as early primary school where parent s may open saving accounts for their children from money received as allowance or gifts during certain festivals or celebration. Thus it is essential that financial institutions to develop and implement strategies which will promote the unit trust investment towards the customers. From this research, we can conclude that the level of customer’s awareness is still moderate which is neither agree nor disagree that they are aware towards unit trust investment. This is because the mean score is 3.1944.We also can conclude that the most influence factor is price. This is because mean score for price is the highest with 3.6440. For the other conclusion, Malaysian citizens are more interested towards unit trust investment compared with foreigner. This is because the mean score for these between two groups, Malaysian citizen are higher with 3.2241, compared with foreigner which is 3.1534. Lastly, we can conclude that all the independent variables (product, promotion, price and place) have coefficient relationship with dependent relationship.